Leaflet - Why should you join the union? - TUC leaflet for women, 1929
1937 1918-1939 "Leaflet - Why should you join the union? - TUC leaflet for women, 1929" [T0154.jpg], c. 1929-1935 This recruitment leaflet for women was distributed by the TUC c.1929-1939